Development of hybrid problem solving method for subsea industry - Md Tohit, Khairul Nizam (2018)
This research is about the development of hybrid problem solving method to identify failures mainly applied in the subsea environment. A3 analysis with support from fishbone diagram and 5 whys analysis techniques were introduced to identify the actual cause of failures. The integration between these two techniques known as a hybrid problem solving method was then applied to identify the actual cause of failures. Upon identification of the actual cause of failure, improvement actions were taken to eliminate the actual cause. In this research, few comparisons in terms of different problem solving methodology applied for different industries namely aerospace, automotive, semi-conductor, chemical and oil and gas industry were reviewed and evaluated to understand the differences for closing the gaps with this new methodology. The proposed hybrid problem solving methodology was validated using a case study. The case study was focusing into the identification of the actual cause of failure related to the Inconel 718 fasteners that were used for Methanol Injection Tree Valve (MITV). Proposal on the lab analysis on fresh and failure fasteners was performed upon reviewing the outcome from the hybrid methodology to ensure the effectiveness of the analysis technique. Few analysis activities were performed consisting of mechanical property evaluation, chemical composition and microstructure review for validating the results. It was identified that the hardness value for Inconel 718 that was applied for this application was 18% higher than the maximum value of 40HRC as stated in MS-607 requirement of material Inconel 718 and API standard 6A718-2009. The data was then compared to understand the characteristics of the failure. One of the steps in the A3 technique is future state and target that requires a mitigation action to eliminate the cause of failure. This was performed by conducting a new material analysis e.g. L7M fasteners for future reference. There is no similar re-occurrence recorded upon implementing the mitigation actions of this problem solving methodology since 2012. This achievement can be concluded as a success of identifying the real cause of failure using hybrid root cause analysis technique. Standard template for subsea's problem solving method was established upon completing the analysis for future use to increase efficiency and reduce cost of failures for each issue in the future.